Source Separation and Decentralization for Wastewater Management - Larsen, Tove; Udert, Kai; Lienert, Judit (IWA Publishing, 2013)
Source Separation and Decentralization for Wastewater Management sets up a comprehensive view of the resources involved in urban water management. It explores the potential of source separation and decentralization to provide viable alternatives to sewer-based urban water management. The book presents a comprehensive view of the state of the art of source separation and ecentralization. It discusses the technical possibilities and practical experience with source separation in different countries around the world. The area is in rapid development, but many of the fundamental insights presented in this book will stay valid.